2017
DOI: 10.1002/nau.23352
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes and risks factors for failure of intradetrusor onabotulinumtoxin A injections for the treatment of refractory neurogenic detrusor overactivity

Abstract: This study confirms long-term efficacy and tolerance of Botox® injection in patients with NDO using CIC. Long-term failure and withdrawal rates remain low but significant, and need to be managed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…(LE 3, GR C). 37 Nevertheless, the multivariate analysis failed to confirm it as an independent long-term risk factor.…”
Section: Maximum Detrusor Pressurementioning
confidence: 97%
See 2 more Smart Citations
“…(LE 3, GR C). 37 Nevertheless, the multivariate analysis failed to confirm it as an independent long-term risk factor.…”
Section: Maximum Detrusor Pressurementioning
confidence: 97%
“…A long-term study with a 7-year follow-up of neurogenic patients confirmed in a univariate analysis that decreased bladder compliance is a risk factor for therapy failure (LE 3, GR C). 37 Moreover, it has been reported that the efficacy of onabotulinumtoxinA injections in patients with low bladder compliance has a shorter duration (12-24 weeks) than in those with normal compliance. 40…”
Section: Bladder Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…In the light of recent data discussed above, we believe there is a need to move towards a new era of managing intradetrusor botulinum toxin injections failures. Besides the options, nicely emphasized in the manuscript by Joussain et al, aiming to optimize BTX‐A intradetrusor injections in order to minimize the failure and discontinuation rates, we believe the aforementioned findings highlight the need to find and properly assess minimally invasive alternatives to augmentation cystoplasty to manage intradetrusor BTX‐A failures and withdrawals.…”
mentioning
confidence: 87%
“…In high risk patients with maximum detrusor pressure greater than 40 cm H 2 O, low bladder compliance, risk of autonomic dysreflexia, recurrent urinary tract infections, and recent changes in the upper urinary tract, it is probably advisable to undertake intradetrusor BTX-A injections under local anesthesia where possible. 6 Though, this would be dependent on local protocols and the changing situation in the country.…”
Section: Neurourology Patients Challenges In Covid-19 Outbreakmentioning
confidence: 99%